The effect of family structure on linkage tests using allelic association. - Whittaker, J C (1998)
We considered the problem of testing a marker for linkage with a disease, using tests based on the transmission-disequilibrium test (TDT). The power of such tests was investigated for a number of possible family types, for which the families were classified by the disease status of family individuals. We show that parental disease status greatly affects the power, with families containing a single affected parent often preferred over families in which neither parent is affected. Families with a pair of affected sibs are of great value for all situations considered, but extension of the TDT to allow inclusion of information from unaffected sibs rarely increases power, if the parents have been genotyped.